2012
DOI: 10.1504/ijep.2012.051215
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of ozone and aerosols to precursor emissions in Europe

Abstract: We modeled the air quality in Europe during June and January 2006 using the MM5/CAMx model system. In this paper, we discuss the sensitivity of ozone and aerosol formation to precursor emissions such as isoprene, NOx, VOC and NH3. Model results suggested that increased isoprene emissions by a factor of four in June 2006 would lead to an increase in afternoon ozone by up to 10% mainly in southern Europe. On the other hand, the effect of increased isoprene emissions on secondary organic aerosols was predicted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The about 3 times higher isoprene emissions in MEGAN led only to up to ~10% (7 ppb) higher ozone mixing ratios in summer compared to the PSI model. Similarly, an earlier study by Aksoyoglu et al (2012) using the PSI model for BVOC emissions suggested that increasing the isoprene emissions by a factor of four in Europe led to an increase of less than 25 10% in the afternoon ozone mixing ratios. The main reason for the weak effect of isoprene on ozone could be that ozone formation in Europe is mostly sensitive to NO x emissions rather than VOC emissions, as well as rather low ozone production compared with background (Oikonomakis et al, 2018; Sartelet et al, 2012).…”
Section: Ozonementioning
confidence: 61%
“…The about 3 times higher isoprene emissions in MEGAN led only to up to ~10% (7 ppb) higher ozone mixing ratios in summer compared to the PSI model. Similarly, an earlier study by Aksoyoglu et al (2012) using the PSI model for BVOC emissions suggested that increasing the isoprene emissions by a factor of four in Europe led to an increase of less than 25 10% in the afternoon ozone mixing ratios. The main reason for the weak effect of isoprene on ozone could be that ozone formation in Europe is mostly sensitive to NO x emissions rather than VOC emissions, as well as rather low ozone production compared with background (Oikonomakis et al, 2018; Sartelet et al, 2012).…”
Section: Ozonementioning
confidence: 61%
“…However, the sensitivity of ozone formation to its precursor emissions might be changing as a result of large NO x emission reductions in Europe since 1990 according to the Gothenburg Protocol. On the other hand, emissions from shipping activities are not regulated as strictly as land emissions and have been increasing continuously, especially in the Mediterranean, affecting both ozone and particulate matter concentrations (Aksoyoglu et al, 2016;Viana et al, 2014).…”
Section: Ozonementioning
confidence: 99%
“…A higher impact is seen in the polluted areas such as the PV region, the Mediterranean coasts in Italy and southeast France (MD region) and the BX region. The Benelux area is exposed to high NO x emissions from both land and shipping activities, leading to a more VOC-sensitive chemical regime for ozone production in this region (Beekmann and Vautard, 2010;Aksoyoglu et al, 2012). The geographical characteristics of the Po Valley in northern Italy led to a trap and accumulation of the pollutants in the area (de Meij et al, 2009a, b;Pernigotti et al, 2012Pernigotti et al, , 2013, which in return can also affect the nearby stations that are located in the MD region.…”
Section: Increased Voc Emissionsmentioning
confidence: 99%